Research on Deformation and Failure Evolution of Deep Rock Burst Drivage Roadway Surrounding Rock under Dynamic Disturbance - Xinggang Xu; Hao Feng; Lishuai Jiang; Tao Guo; Xingyu Wu; Zequan Sun (Shock and Vibration)
In order to explore the deformation and failure evolution characteristics of the surrounding rock during the connection process of the deep rock burst drivage roadway under the dynamic load disturbance, and based on this, the catastrophe mechanism of the roadway is analyzed, taking the rock burst accident of Longyun Coal Industry in Shandong Province on October 20, 2018, as the engineering background. FLAC3D was used to study the distribution evolution law of displacement, plastic zone, and stress field in the whole process of “Roadway Drivage-Deformation and Failure-Instability and Disaster” in the surrounding rock of deep roadway. The research results show that under the conditions of high stress and dynamic load disturbance, the surrounding rock deformation and failure are significant during the connection of the thick-top-coal roadway in deep, the roof is the most, the two ribs are the second, and the roadway top-coal is in an “inverted trapezoid” sag pattern. When the length of the bolts is limited or the anchoring force of the cables is not enough to effectively restrain the roof, the impact of dynamic disturbance on the plastic damage of the roof is greater than that of the two ribs and the floor, and the plastic damage of the coal seam roof affecting the surrounding rock deformation of the roadway drivage played a leading role.